Reestruturação do sistema penitenciário no estado do Maranhão: uma análise das mudanças no Complexo de Pedrinhas e na Unidade Prisional de Codó e o impacto da ADPF Nº. 347/DF - França, Suelen dos Santos (2024)
The Brazilian penitentiary system, especially at the state and municipal level, faces a chaotic reality, marked by human rights violations that have lasted for decades. Various challenges, such as overcrowding in prisons, unsanitary conditions in facilities, inadequate and insufficient food supply, the occurrence of torture and collective punishments, as well as the recruitment of inmates by criminal factions, are just a few examples of the chronic problems routinely observed in most institutions. of detention. Given this scenario, we know that the Maranhão prison system between 2010 and peaking in 2013 made national and international headlines, demonstrating the chaos in Maranhão's prisons. This resulted in several rebellions, beheadings, murders, with complaints to the UN, CNJ and international pressure, strengthened by the feeling of impotence among families and society in general. It was a true scene of war and terror in a country marked by peace on its territory. There were also reports from detainees of torture, rape of family members, procedural delays and corruption. After 10 years, the Maranhão penitentiary system involving the Executive, Judiciary, organized civil society, OAB and others, implemented a series of changes, adopting a management model aimed at restructuring the Maranhão system. In this sense, the present study has the general objective of presenting which strategies were used to restructure the Maranhão prison system, which, despite facing difficulties, changed the prison scenario. We left the scenes of beheadings to reach 1st place nationally in education and work activities in the prison environment, with countless innovations. Furthermore, the objective of this research is also to present the ADPF 347 – State of Unconstitutional Things. This is a research with a bibliographical, qualitative approach, in which we carried out our analyzes based on reports from inmates and system employees for more than 10 years, in the period from November 2023. In the first chapter, we bring some notes about the history of Criminal Law on a global, Western and national level, delving deeper into Michel Foucault's perceptions about the prison system in the world. We present some considerations about the reality of the Brazilian penitentiary system. In the second chapter, we address the reality of the Brazilian prison system with a focus on the State of Maranhão, entering the prison reality of two prison units in the state: Pedrinhas penitentiary complex and Codó Prison Resocialization Unit. In the following chapter, we present the restructuring actions applied throughout the state, such as the construction and renovation of prisons, formation of strategic groups, separation of prisoners, management of processes involving incarcerated defendants, formation of groups for analysis, qualification of civil servants, material and better procedural monitoring of the conclusion of processes, analysis of benefits and extinction of sentences. And, finally, an approach to the judgment on the merits of the Claim of Non Compliance with Fundamental Precept (ADPF) de nº. 347, which recognized the existence of the Unconstitutional State of Things in the Brazilian prison system and its implications for the State of Maranhão.